DESERTIFICATION AND ITS IMPACT ON THE SITUATION OF AGRICUITURE AND VEGETATION IN IRAQ IN PERIOD FORM (1980-2010) - Salim Al-Youzbaki; Ali Subhie Abbas Al-Mshhdani (Mesopotamia Journal of Agriculture)
Desertification and its impact on the situation of agriculture and vegetation in Iraq in period form (1980-2010). Mesopotamia J. of Agric., Vol. (43) No. (1) 2015: 33-41. The wilderness is a dangerous environmental phenomenon, as well as it has became the most dangerous challenges which have faced the humanity in this century, because its negative effects on many countries especially these areas which have arid, or semi arid, and even semi humid climate, so this study has aimed to show the reasons and factors for this problem, where the economic and natural factors have played great role in existing this phenomenon the wild areas in Iraq have amounted (38,5%), and threatened with wilderness have amounted (54,4%) from the total area of Iraq. The problem of this research has included growing and increasing these wilderness & threatened with wilderness areas because of the negative effects (not appropriate) for the mentioned factors. This research has gained its importance from this situation which witnessed increasing the size of wilderness and its effect on the reduced agricultural production, losing of the cultivated areas, and its effect on the environment and the other social & economic conditions. In regard of increasing the size of wilderness in Iraq, a serious facing to prevent this problem must be taken, putting the solutions and treatments of it. Thus this study has depended on a hypothesis to the effect that there are several economic and natural (human) factors are contributing with different effects in growing the wilderness areas in Iraq during (1980_2010). This research aims to identify the nature of wild areas, its forms, and reasons in Iraq, the quantitative measurement for the factors impacting on this phenomenon in Iraq, and showing the different effects of this phenomenon, in addition to show the methods of treating the wilderness in Iraq. Conclusions have been reached are follows: Iraq is suffering from deficiency of water, therefore the farmers have resorted to use non beneficial water to irrigate the crops, and there are declining in plant cover because of the arid conditions, human factors, mismanagement of soil and water, arbitrary posturing, and the dust. The study has reached to several recommendations such as: educating of farmers to interest with agricultural lands, their production, and how treating with them through holding the seminars, field visits, prohibiting the wrong methods, committing with water rationed instruments for each crops to limit the problem of salts, encouraging to make repellents to protect the planted and postured areas, and more interesting with plant cover.